Enhanced Electronic Properties of Pt@Ag Heterostructured Nanoparticles - Koichi Higashimine; Shinya Maenosono; Derrick M. Mott; Anh Thi Ngoc Dao (Sensors, 2013)
Platinum coated by silver nanoparticles was synthesized, which displays a unique structure where polycrystalline platinum particles are completely encapsulated in continuous monocrystalline silver shells. These particles display accentuated electronic properties, where the silver shells gain electron density from the platinum cores, imparting enhanced properties such as oxidation resistance. This electron transfer phenomenon is highly interfacial in nature, and the degree of electron transfer decreases as the thickness of silver shell increases. The nanoparticle structure and electronic properties are studied and the implication to creating sensing probes with enhanced robustness, sensitivity and controllable plasmonic properties is discussed.